Rotavirus-Specific Maternal Serum Antibodies and Vaccine Responses to RV3-BB Rotavirus Vaccine Administered in a Neonatal or Infant Schedule in Malawi - Benjamin Morgan; Eleanor A. Lyons; Amanda Handley; Nada Bogdanovic-Sakran; Daniel Pavlic; Desiree Witte; Jonathan Mandolo; Ann Turner; Khuzwayo C. Jere; Frances Justice; Darren Suryawijaya Ong; Rhian Bonnici; et al. (Viruses)
High titres of rotavirus-specific maternal antibodies may contribute to lower rotavirus vaccine efficacy in low- and middle-income countries (LMICs). RV3-BB vaccine (G3P[6]) is based on a neonatal rotavirus strain that replicates well in the newborn gut in the presence of breast milk. This study investigated the association between maternal serum antibodies and vaccine response in infants administered the RV3-BB vaccine. Serum was collected antenatally from mothers of 561 infants enrolled in the RV3-BB Phase II study conducted in Blantyre, Malawi, and analysed for rotavirus-specific serum IgA and IgG antibodies using enzyme-linked immunosorbent assay. Infant vaccine take was defined as cumulative IgA seroconversion (≥3 fold increase) and/or stool vaccine shedding. Maternal IgA or IgG antibody titres did not have a negative impact on vaccine-like stool shedding at any timepoint. Maternal IgG (but not IgA) titres were associated with reduced take post dose 1 (p < 0.005) and 3 (p < 0.05) in the neonatal vaccine schedule group but not at study completion (week 18). In LMICs where high maternal antibodies are associated with low rotavirus vaccine efficacy, RV3-BB in a neonatal or infant vaccine schedule has the potential to provide protection against severe rotavirus disease.